Tolak Bala Pandemi Virus Corona pada Masyarakat Melayu di Desa Rawak Kabupaten Sekadau Kalimatan Barat - Karmila Karmila; Diaz Restu Darmawan; Efriani Efriani (Ideas Publishing, 2021)
The tradition of Tolak Bala from the Malay community in Rawak Village, Sekadau Hulu District, Sekadau Regency is still often carried out even though they are already predominantly Muslim. The Tolak Bala tradition is a religious syncretism, where in the ritual can be found elements of Islam, as well as animist beliefs and dynamism. This study aims to determine and describe the function of the Tolak Bala ritual in relation to the Corona virus pandemic. The method used in this study is a qualitative method and data collection techniques using observation and interviews. The findings of this study have shown that the Tolak Bala ritual has changed in meaning because knowledge and mindsets about religion in the people of Rawak Village have become more advanced. They began to believe that the Tolak Bala ritual process carried out in ancient times was contrary to religious law or Islamic law. In the past, the ritual process of Tolak Bala ritual carried out with animistic worship, while nowadays it is carried out by praying to Allah SWT. Tradisi tolak bala masyarakat Melayu di Desa Rawak Kecamatan Sekadau Hulu Kabupaten Sekadau masih sering dilakukan meskipun mereka sudah mayoritas beragama Islam. Tradisi tolak bala ini merupakan sinkretisme agama yang dalam ritual tersebut dapat ditemukan unsur-unsur Islam, serta kepercayaan animisme dan dinamisme. Penelitian ini bertujuan untuk mengetahui serta mendeskripsikan fungsi dari ritual tolak bala dalam hubunganya dengan pandemi virus corona. Metode yang digunakan dalam penelitian ini adalah metode kualitatif serta teknik pengumpulan data menggunakan observasi dan wawancara. Temuan penelitian ini telah menunjukkan bahwa ritual tolak bala mengalami perubahan makna karena pengetahuan dan pola pikir tentang agama pada masyarakat di Desa Rawak sudah semakin maju. Mereka mulai meyakini bahwa proses ritual yang dilakukan pada zaman dahulu itu bertentangan dengan hukum agama atau syariat Islam. Pada zaman dulu proses ritual tolak bala dilakukan dengan pemujaan secara animism, sedangkan zaman sekarang dilakukan dengan proses berdoa kepada Allah Swt.